Diamonds, Cloverleafs, and SPUIs: The Geography of Freeway Interchanges in the United States - Weber, Joe (The Professional geographer, 2022)
Freeway interchanges are a fundamental component of freeway networks and provide nodes for economic development. They take a wide range of forms, including diamonds, cloverleafs, and stacks, depending on traffic conditions and other factors. They have not been the subject of study or data collection, however, and their numbers are unknown. Their geography is examined using nationwide data that allow the location and type of every interchange to be identified. The results show that there are more than 25,000 freeway interchanges in the United States, with diamond configurations accounting for almost 61 percent of them. They are far more common in urban areas. Interchanges have been modified or replaced at a steady rate and continue to grow in number. Although frequently overlooked, they are some of the sites of greatest congestion in the country and some of the most expensive transport infrastructure elements ever built.